The burden of bleeding in haemophilia: is one bleed too many?. (29th January 2014) - Gringeri, A.; Ewenstein, B.; Reininger, A.
Summary Joint bleeding is the hallmark of haemophilia. Increasingly, the pain, restricted movement and anxiety provoked by even a single haemarthrosis are concerns for patients, families and treating physicians. The aims of this study were to determine whether the current paradigm for prophylaxis requires a shift in focus from reducing the frequency of bleeding episodes to a goal of zero bleeding and to review and discuss the published data from in vitro and animal experiments and clinical studies in patients with haemophilia that describe the impact of joint bleeding. More than two to three bleeding into the same joint may cause irreversible and progressive structural damage that compromise health‐related quality of life (HRQoL). A goal of zero bleeding episodes – or as close to zero as possible – is key to enhancing joint health and HRQoL in children and adults with haemophilia. Achieving this goal requires individualized, outcome‐based, multidisciplinary care to maximize prophylactic efficacy without increasing overall health care costs.